2017
DOI: 10.15406/jpnc.2017.06.00249
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Nutritional Status of Bottle-Fed Infants and the Prevalence of Infections, Allergy and Diarrhea among Bottle Fed Infants and Its Comparison with Exclusively Breast Fed Infants Aged 0-6 Months

Abstract: Title: Assessment of the Nutritional Status of Bottle-fed Infants and the prevalence of infections, allergy and diarrhea among them and its comparison with exclusively breast fed inafants aged 0-6 months. Background: For the past few years, the rate of bottle-feeding practice during the first six months of the child's life has shown a sharp increase, which necessitated to conduct a study to highlight the nutritional status of bottle-fed infants. Objectives: To assess the nutritional status of infants who are b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Various studies evidenced better cognitive development and intelligence quotients in breastfed infants compared to bottle-feed ones [ 6 ]. Previous studies have shown that bottle-feeding was a key factor for child morbidity and mortality in different settings [ 7 ], [ 8 ], [ 9 ]. For example, in the Philippines bottle-fed infants were found to be at high risk of hospitalisation due to infections [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Various studies evidenced better cognitive development and intelligence quotients in breastfed infants compared to bottle-feed ones [ 6 ]. Previous studies have shown that bottle-feeding was a key factor for child morbidity and mortality in different settings [ 7 ], [ 8 ], [ 9 ]. For example, in the Philippines bottle-fed infants were found to be at high risk of hospitalisation due to infections [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Infants who are bottle fed are 2.8 times more likely to develop gastrointestinal [21] . A study by Hussain Z Khan et al [22] , diarrhea was more common in BF infants than in exclusively breastfed (EBF) infants as it shows that in BF infants 26% were suffering from diarrhea whereas 24% EBF infants were suffering. In present study it was found that patients with grade 1 malnutriton 9 (52.9%)suffered from no dehydration and 8(47.1%) suffered some dehydration.…”
Section: Table No 4 Discussionmentioning
confidence: 99%
“…Breastfeeding, particularly when exclusive and prolonged, protects against severe morbidities such as diarrhea and respiratory infections [4]. Various studies documented that bottle-feeding is associated with child morbidity (e.g., diarrhea, respiratory infection, and allergies) and mortality [9], [10], [43], [44], [45], [46]. For example, in Sudan, bottle-fed children were at high risk of malnutrition and hospitalization due to infectious causes as 83.3% of hospitalized children used bottle feeding [9].…”
Section: Discussionmentioning
confidence: 99%
“…After participant acceptance and success in fulfilling the study inclusion criteria, a questionnaire was applied to collect relevant information from mothers through a face-to-face interview. The questionnaire was developed based on the previous studies [9], [10], [11], [12], [13], [14], [15], [16], [17], [18], [19]. It included demographics (e.g., education, age, and occupation), mode of delivery (vaginal delivery, and cesarean delivery), infant's information (e.g., age, gender, and history of hospitalization over the past 6 months), and the main cause for hospitalization.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation